A comparative study between proximal femur locking compression plate and dynamic hip screw fixation in management of pertrochanteric fracture - Harshwardhan, Hemeshwar; Mali, Sawai ingh; Sharma, Manish (International Journal of Research in Orthopaedics, 2019)
Background: Pertrochanteric fracture is common in elderly people. Dynamic hip screw is still considered the gold standard for treating intertrochantric fracture. Proximal femoral locking compression plate is newer device. The purpose of the study was to compare the outcome of surgical treatment of trochanteric fracture by dynamic hip screw and proximal femoral locking compression plate. Methods: We study 60 patient admitted and followed up at J.L.N. Medical College Ajmer from June 2016 to April 2018 for minimum 6 month or till the bony union. Every fracture classified according to AO classification and functional result will be assessed according to Harris hip score using unpaired t test. Results: The mean operative time and average intraoperative blood loss was more in PFLCP group when compared with DHS group it was statically significant. DHS group has marginally better functional result then PFLCP group. There was no difference in the radiological outcome between two group. Conclusions: DHS is best implant for stable intertrochantric fracture but PFLCP can also be good alternative for unstable IT femur fracture.